DESIGN AND ANALYSIS WEBSITE TEACHERS HIGH SCHOOL (CASE STUDY SMAN 2 PANGKALAN BUN KOTAWARINGIN BARAT CENTRAL KALIMANTAN) - Gunawan, Vincentius Abdi; Sahay, Abertun Sagit (Universitas Palangka Raya, 2015)
With the growing world of technology and information, many teachers use LCD projectors inperforming its duties. However, many students want to file material used by the teacher. Not infrequentlythe student fails to obtain the file. Seeing these conditions, the National High School 2 Pangkalan Bunhas a website that is intended for all students to acquire learning materials and also the announcement ofwhich is managed by the teacher.In the analysis and design of this school website, software development method used is LinearSequential or too waterfall. The steps followed in this method include taapan analysis and design phases.Unified Modeling Language (UML) is used this stage which is a tool in the process. UML diagrams usedare usecase diagrams, activity diagrams and class diagrams.From the analysis and design, looks actor who created are teachers, visitors and admin. Usecaseproduced is manage announcements, news management, material management, profile management,governance subjects for teachers actor. As for the actor admin usecase that there is a teacher accountmanagement. As for the visitors just biased view news, announcements, download the material and seethe teacher profile.